Zakat allocation system using fuzzy logic / Siti Farah Nasehah Mukhlis - Siti Farah Nasehah, Mukhlis (2012)
Zakat is one of the five pillars in Islam. It is a fixed proportion collected from the extra wealth and earnings of a Muslim, which is then distributed to the prescribed receiver, also known as asnaf. To this day, determining qualification for zakat applicants is done in meetings by the zakat officials. The application of zakat follows a meticulous procedure as stated in the syarak. The objectives of this research are to build a fuzzy expert system for zakat allocation by implementing the fuzzy inference technique and to investigate the effectiveness of the fuzzy expert system in decision making for the zakat applicant’s qualification. The research focuses on calculating zakat for the rural area within the Sri Iskandar jurisdiction. The asnaf selected is the poor (fakir) and needy (miskin) and the zakat aid selected is monthly financial aid. The aim of this research is to use fuzzy logic to aid in the decision making of the zakat councils. The methodology for the project system is to use fuzzy logic to find the corresponding rules that can give a result of whether the applicant is qualified or not. Besides that, the range for the amount of zakat is suggested. The result that was obtained from this fuzzy system was a success of 66.67 per cent. The remaining percentage is the inconsistency. Nevertheless, the possibility that a fuzzy expert system can be used for the zakat institution in the near future is promising.